Neoliberalism and rationality: a tango for two?. Issue 3 (2nd October 2021) - Papageorgiou, Theofanis; Koskoletos, Sotiris; Papangelopoulos, Antonis
Abstract : Questions about the role that rationality plays in economics are of general importance. In that vein, we check for differences in the concept of rationality, in parallel with differences in the concept of neoliberalism, in the aftermath of the crisis, arguing that different conceptions of rationality go hand in hand with variations of neoliberalism. Furthermore, we argue that in periods of crisis there is a tendency to greater merging of morality with utility maximization theory, mainly driven through the de jure moralization of punishment instead of de facto utilitarian punishment. Classical neoliberal notions, such as ' homo economicus ', entrepreneurship, freedom, and rationality may still exist; while they are continuously redefined towards narrower conceptualizations encompassing moral, totalizing and punitive aspects of subjectivity and power; among others. In parallel, the value of life has significantly diminished, putting lethality and death at the center of neoliberal reproduction. After the outburst of the crisis, a prominent tendency towards moralization of subjectivity by default, de jure punishment and social stigmatization facilitated the answer to the question 'who is going to pay', the finding of the guilty subject, i.e. the subject that is going to pay for the crisis irrespective of whether it is really to blame or not.